Policing mandatory bicycle helmet laws in NSW: Fair cop or unjust gouge?. (December 2020) - Hogg, Russell; Quilter, Julia
Australia was the first country to introduce laws mandating the wearing of helmets by bicyclists with the aim of enhancing road safety for cyclists. Examining the law and its administration in NSW, we point to some serious problems and anomalies with the law. We argue safety concerns have been relegated and the fine for the offence has lost any sense of proportionality with offending, parity with penalties imposed in other states and with penalties for other road safety offences in NSW. We also discuss concern over potential police misuse of the law and of its collateral consequences for the vulnerable.